# Example 25 - Chapter 4 Class 12 Determinants (Term 1)

Last updated at May 29, 2018 by Teachoo

Examples

Example 1

Example 2

Example 3

Example 4

Example 5 Important

Example 6 Deleted for CBSE Board 2022 Exams

Example 7 Deleted for CBSE Board 2022 Exams

Example 8 Deleted for CBSE Board 2022 Exams

Example 9 Important Deleted for CBSE Board 2022 Exams

Example 10 Important Deleted for CBSE Board 2022 Exams

Example 11 Deleted for CBSE Board 2022 Exams

Example 12 Deleted for CBSE Board 2022 Exams

Example 13 Deleted for CBSE Board 2022 Exams

Example 14 Important Deleted for CBSE Board 2022 Exams

Example 15 Important Deleted for CBSE Board 2022 Exams

Example 16 Important Deleted for CBSE Board 2022 Exams

Example 17

Example 18 Important

Example 19

Example 20

Example 21

Example 22 Important

Example 23

Example 24 Important

Example 25 You are here

Example 26 Important

Example 27

Example 28 Important

Example 29

Example 30 Deleted for CBSE Board 2022 Exams

Example 31 Important Deleted for CBSE Board 2022 Exams

Example 32 Important Deleted for CBSE Board 2022 Exams

Example 33 Important

Example 34 Important Deleted for CBSE Board 2022 Exams

Chapter 4 Class 12 Determinants (Term 1)

Serial order wise

Example 25 If A = 2 3 1 4 and B = 1 2 1 3 , then verify that (AB)-1 = B-1 A-1 Taking L .H.S (AB) 1 First calculating AB AB = 2 3 1 4 1 2 1 3 = 2 1 +3( 1) 2 2 +3(3) 1 1 +( 4)( 1) 1 2 + 4 3 = 2 3 4+9 1+4 2 12 = 1 5 5 14 Now, (AB)-1 = 1 |AB| adj (AB) exists if |AB| 0 |AB| = 1 5 5 14 = (-1)(-14) 5(5) = 14 25 = 11 Since |AB| 0 (AB)-1 exists AB = 1 5 5 14 adj (AB) = 1 5 5 14 = 14 5 5 1 Now, (AB) 1 = 1 |AB| adj (AB) Putting values = 1 11 14 5 5 1 = 1 11 14 5 5 1 Taking R.H.S B-1A-1 First Calculating B 1 B = 1 2 1 3 B = 1 |B| adj (B) exists if |B| 0 |B| = 1 2 1 3 = 3 2 = 1 Since |B| 0 , B-1 exist B = 1 2 1 3 adj (B) = 1 2 1 3 = 3 2 1 1 Now, (B) 1 = 1 |B| adj (B) Putting values = 1 1 3 2 1 1 = 3 2 1 1 Finding A-1 A-1 = 1 |A| adj (A) exists if |A| 0 |A| = 2 3 1 4 = 2 ( 4) 1( 3) = 8 3 = 11 Since |A| 0 , A 1 exists A = 2 3 1 4 adj (A) = 2 3 1 4 = 4 3 1 2 Now, A-1 = 1 |A| adj (A) = 1 11 4 3 1 2 = 1 11 4 3 1 2 Thus, B-1A-1 = 3 2 1 1 1 11 4 3 1 2 = 1 11 3 2 1 1 4 3 1 2 = 1 11 3 4 +2(1) 3 3 +2( 2) 1 4 +1(1) 1 3 +1( 2) = 1 11 12+2 9 4 4+1 3 2 = 1 11 14 5 5 1 = L.H.S L.H.S = R.H.S Hence proved